Glycaemic status and depressive symptoms among adults in Germany: results from the German Health Interview and Examination Survey for Adults (DEGS1). Issue 11 (28th June 2018) - Weikert, B.; Buttery, A. K.; Heidemann, C.; Rieckmann, N.; Paprott, R.; Maske, U. E.; Scheidt‐Nave, C.; Busch, M. A.
Abstract: Aims: To examine the association between glycaemic status and depressive symptoms in a nationwide sample of the adult population in Germany. Methods: We conducted a cross‐sectional analysis of data from 6385 participants aged 18–79 years in the nationwide German Health Interview and Examination Survey for Adults 2008–2011 (DEGS1). Glycaemic status was classified as follows: diagnosed diabetes (self‐reported diagnosis or receiving antidiabetes medication); undiagnosed diabetes (HbA1c ≥48 mmol/mol [≥6.5%]); prediabetes (HbA1c 39–47 mmol/mol [5.7–6.4%]); or normoglycaemia (HbA1c <39 mmol/mol [<5.7%]). Current depressive symptoms were measured using the Patient Health Questionnaire depression scale (PHQ‐9) and defined as elevated depressive symptoms (PHQ‐9 score ≥10 points; dichotomous variable) and severity of depressive symptoms (PHQ‐9 score, range 0–27 points; continuous variable). Associations of glycaemic status and HbA1c with both depressive symptoms variables were analysed using multivariable logistic (elevated depressive symptoms) and linear (severity of depressive symptoms) regression models. Results: Compared with normoglycaemia, diagnosed diabetes, but not prediabetes or undiagnosed diabetes, was associated with elevated depressive symptoms (odds ratio 1.55, 95% CI 1.00–2.41) and severity of depressive symptoms (β coefficient 0.71, 95% CI 0.23–1.19) in models adjusting for sociodemographics and health behaviours. Associations were similar among people with diagnosed diabetes taking and not taking antidiabetes medication. Among people without diagnosed diabetes, no associations between HbA1c and depressive symptoms were found. Conclusions: Diagnosed diabetes, but not prediabetes, undiagnosed diabetes or HbA1c, was associated with depressive symptoms among adults in Germany. Studies examining psychosocial and biological mechanisms that may potentially explain relationships between diagnosed diabetes and depressive symptoms are needed. What's new?: We examined associations between glycaemic status and current depressive symptoms measured using the Patient Health Questionnaire depression scale (PHQ‐9) in a nationwide representative study of 6385 adults aged 18–79 years in Germany. Compared with normoglycaemia, diagnosed diabetes, but not prediabetes or undiagnosed diabetes, was associated with elevated depressive symptoms (PHQ‐9 score ≥10: odds ratio 1.55, 95% CI 1.00–2.41) and severity of depressive symptoms (PHQ‐9 score: β coefficient 0.71, 95% CI 0.23–1.19) in models adjusting for sociodemographics and health‐related behaviours. Among people without diagnosed diabetes, HbA1c was not associated with depressive symptoms. This study provides evidence that diagnosed diabetes may have stronger associations with depressive symptoms than glucose metabolism alone.